An effect of sweep angle on roll damping derivative for a Delta wing with curved leading edges in unsteady flow - Monis, Renita Sharon; Crasta, Asha; Khan, Sher Afghan (Transstellar Journal Publications and Research, 2019)
This paper presents the results of an analytical study to account the effect of the sweep angle of a delta wing whose leading edges are curved on roll damping derivative at various angles of attack and the amplitude of the full sine waves. In the present theory, the effect of Leeward surface has been taken into consideration with the attached shock case at the leading edge. For a detached shock case, this theory will not be valid. Results have been obtained for the hypersonic flow of perfect gases over a wide range of angle of attack and the Mach number. The results indicate that the roll damping derivative decreases with a sweep angle, but increase with the increase in the flow deflection angle δ as well as with Mach M.